Помогите не пойму как решать ! (4а^2+9а)-(а^2 -1+9а)                                                 6а^4-2а^2(3а^2+а)                                                  ху(х-у)-2ху(х+у)

Помогите не пойму как решать ! (4а^2+9а)-(а^2 -1+9а)                                                  6а^4-2а^2(3а^2+а)                                                   ху(х-у)-2ху(х+у)
Гость
Ответ(ы) на вопрос:
Гость
(4а^2+9а)-(а^2 -1+9а)=4a^2+9a-a^2+1-9a=3a^2+1 6а^4-2а^2(3а^2+а)=6a^4-6a^4-2a^3=-2a^3 ху(х-у)-2ху(х+у)=x^2y-xy^2-2x^2y-2xy^2=-x^2y-3xy^2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы